2021
DOI: 10.3390/world2020018
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Sustainable Pesticide Control in Brazil

Abstract: If the current policy explores the utilization of active ingredients in use quickly and to the maximum, the same does not occur with the ban on the registration of products highly dangerous to both health and the environment. The current policy does not aim at reducing pesticide toxicity and ecotoxicity, required to reduce environmental contamination and human exposure. To this end, it is essential to adjust scientific evaluation parameters concerning lower concentration tolerance limits to modernity standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Many of the papers were country-speci c studies of paraquat regulations and their effect; others were general studies of pesticide regulations and their effects and implementation, which included discussions of paraquat regulations. Among the country-speci c papers, the results were dominated by case studies from Sri Lanka (23,(26)(27)(28)(29)(30), South Korea (31)(32)(33)(34)(35), Taiwan (36, 37), Japan (24,38), and Brazil (39,40). Several papers presented regional and global overviews (1,(41)(42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Documents Identi Edmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the papers were country-speci c studies of paraquat regulations and their effect; others were general studies of pesticide regulations and their effects and implementation, which included discussions of paraquat regulations. Among the country-speci c papers, the results were dominated by case studies from Sri Lanka (23,(26)(27)(28)(29)(30), South Korea (31)(32)(33)(34)(35), Taiwan (36, 37), Japan (24,38), and Brazil (39,40). Several papers presented regional and global overviews (1,(41)(42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Documents Identi Edmentioning
confidence: 99%
“…In Brazil, in 2015, the National Health Surveillance Agency (ANVISA) concluded that paraquat should be banned due to the high numbers of acute poisonings and the links to Parkinson's disease (40,74). In 2017, the Collegiate Directorship Resolution 177/2017 imposed a complete ban on paraquat starting from 2020 (75).…”
Section: Phase-outs and Bansmentioning
confidence: 99%
“…Simultaneamente, é preciso a conscientização dos produtores. Como apontado por Langenbach et al (2021), para que haja transição agroecológica, é preciso que, juntamente com o desenvolvimento de tecnologias sustentáveis, haja um processo de conscientização dos produtores.…”
Section: Discussão Dos Resultadosunclassified